RELAYTM Branched–International Results of Vessel Patency and Reintervention - Singh, Sidhant; Surkhi, Abedalaziz O.; Tan, Sven Z. C. P.; Jubouri, Matti; Bailey, Damian M.; Williams, Ian; Bashir, Mohamad (Frontiers in Cardiovascular Medicine, 2022)
Background Surgical intervention remains the mainstay treatment for aortic arch aneurysm and dissection, but the high mortality and morbidity rates have led to a need for the development of minimally invasive alternatives to arch reconstruction. RELAY™ Branched (Terumo Aortic, Inchinnan, UK) represents a viable option for complex endovascular aortic arch repair. We present multi-centre data from Europe documenting the efficacy of the endograft in terms of its target vessel patency and reintervention rates. Methods Prospective data collected between January 2019 and January 2022 associated with patients treated with RELAY™ single-, double-, and triple-branched endoprostheses from centres across Europe was retrospectively analysed with descriptive and distributive analysis. Follow up data from 30 days and 6-, 12-, and 24 months postoperatively was included. Patient follow up was evaluated in terms of target vessel patency and reintervention rates. Results Technical success was achieved in 147 (99.3%) cases. Over 24 months period, target vessel patency was maintained in 80.2% (n = 118) of patients. Target vessel cannulation was achieved in 146 (99.3%) cases. Over the 24-month follow-up period, 30 reintervention procedures were required, of which 29 (97%) took place within the South Europe region which accounted for 19.6% (n = 29) of total cases. Zero reinterventions were required in patients that were treated with single- or triple-branched endoprostheses. Discussion The data presented herein demonstrates that RELAY™ Branched is a technically efficacious device for endovascular aortic arch repair and is associated with favourable target vessel patency and reintervention rates. Key design features of the endoprosthesis and good perioperative management can contribute greatly to mitigating reintervention and loss of vessel patency following endovascular aortic arch repair.